Estimating the potential of rainfed agriculture in India: prospects for water productivity improvements - Sharma, Bharat R.; Rao, K.V.; Vittal, K.P.R.; Ramakrishna, Y.S.; Amarasinghe, Upali A. (Elsevier, 2010)
A detailed district and agro-ecoregional level study comprising the 604 districts of India was undertaken to (i) identify dominant rainfed districts for major rainfed crops, (ii) make a crop-specific assessment of the surplus runoff water available for water harvesting and the irrigable area, (iii) estimate the efficiency of regional rain water use and incremental production due to supplementary irrigation for different crops, and (iv) conduct a preliminary economic analysis of water harvesting/supplemental irrigation to realize the potential of rainfed agriculture. A climatic water balance analysis of 225 dominant rainfed districts provided information on the possible surplus runoff during the year and the cropping season. On a potential (excluding very arid and wet areas) rainfed cropped area of 28.5 million ha, a surplus rainfall of 114 billion m3 (Bm3) was available for harvesting. A part of this amount of water is adequate to provide one turn of supplementary irrigation of 100 mm depth to 20.65 Mha during drought years and 25.08 Mha during normal years. Water used in supplemental irrigation had the highest marginal productivity and increase in rainfed production above 12% was achievable even under traditional practices. Under improved management, an average increase of 50% in total production can be achieved with a single supplemental irrigation. Water harvesting and supplemental irrigation are economically viable at the national level. Net benefits improved by about threefold for rice, fourfold for pulses and sixfold for oilseeds. Droughts have very mild impacts on productivity when farmers are equipped with supplemental irrigation.